The activeness, critical, and creative thinking skills of students in the Lesson Study-based inquiry and cooperative learning - Hasan, Rusdi; Lukitasari, Marheny; Utami, Sri; Anizar, Anizar (University of Muhammadiyah Malang, 2019)
The implementation of innovative learning and lesson study (LS) are potential to improve student thinking skills and activeness differently and mostly implemented separately. This study aimed to explore and compare the student critical and creative thinking skills as well as student activeness in the inquiry and cooperative models combined with LS-based learning practice. This was a descriptive quantitative study that was conducted at Islamic Senior High School 1 of Bengkulu. The sample was two classes consisted of 33 and 32 students each that conducted LS-inquiry and LS-cooperative learning. The essay test delivered to measure critical and creative thinking skills and observation sheet to measure student activeness. The data were analyzed by t-test to compare critical and creative thinking skills as well as the student activeness between the LS-inquiry and LS-cooperative classes. The result showed that LS-inquiry learning improved the student critical and creative thinking skills that significantly higher than LS-cooperative learning. The student activeness improved gradually as LS cycles during learning processes in either inquiry or cooperative learning, but no significant difference between these two learning models. It showed that inquiry learning plays a dominant influence in critical and creative thinking skills improvement, whereas LS in student activeness improvement otherwise.